Клинико-экспериментальное обоснование рациональности использования нейропротекторной терапии при лечении ятрогенного компресионно-токсического поражения нижнего альвеолярного нерва пломбировочными материалами - Погоріла, Анна Василівна; Шінкарук-Диковицька, Марія Михайлівна; Мунтян, Олена Вікторівна (Actual Dentistry, 2019)
Resume. Damage of the periapical tissues and lower alveolar nerve during endodontic manipulation is a common complication among practitioners of dentistry. Therefore, the expediency of developing and introducing new methods of treatment of iatrogenic compression-toxic lesions of the lower alveolar nerve, by appointment in the complex therapy of neuroprotectors, whose purpose is to increase the tolerance of the nervous tissue to the action of pathogenetic factors, is appropriate and relevant. The aim: to evaluate the magnitude of the neuroprotective activity of amantadine hydrochloride in the experimental iatrogenic compression-toxic lesions of the lower alveolar nerve with sealing materials of rabbits by changing the titers of NSE and protein S100 and assessing the possibility of its use for a new purpose under conditions of this pathological condition in the clinic. In the clinical trial 20 patients with a diagnosis of acute neuropathy of the lower alveolar nerve filling stuff and 5 patients in the control group (practically healthy, without general somatic diseases and neurological status) participated. Age of patients 25–60 years of age, male. An experimental study was conducted on 21 experimental animals (rabbits of the Chinchilla breed). Diagnostics of neuromarker activity of titres of neuron-specific enolase and S100 protein during neuroprotective treatment was performed using a solid-phase enzyme-linked immunosorbent assay using the kit ELISA KIT (DAI, USA) on the Hipson (Czech Republic) device. When mechanical and toxic effects of filling materials on the basis of resorcin-formalin and epoxy resin, destructive degenerative changes in the nervous tissue arise, as evidenced by neuromarker escalation (NSE, titer protein S100) for 14 days as a clinical and experimental study. Drug treatment along with rational surgical intervention – improves the course of this pathology, but with the attraction of amantadine hydrochloride to the scheme of neuroprotector based on the amantadine hydrochloride, the restoration of the structural and functional state of the NAS is significantly improved, as evidenced by the data obtained. As a result of conducted clinical and experimental studies, based on the results of immunoassay determination in blood serum, changes in activity and titres of neuromarkers (NSE and protein S100) in the dynamics of iatrogenic compression - toxic lesions of the lower alveolar nerve with sealing materials, allows us to stimate the presence and depth of destructive degenerative changes in its fibers, and hence - can be used for express diagnosis, therapeutic efficacy and possible prognosis of the disease. When removing the filling material for apex in the lower alveolar nerve, it is necessary to conduct a rational treatment quickly (up to 14 days inclusive), to prevent the occurrence of non-inverse processes in the nerve. Attracting amantadine hydrochloride (100 mg 2p/d) to a complex Therapy drug, improves the progress of regenerative processes in damaged nerve areas, along with improved clinical outcomes of patients (pain reduction, feeling of numbness). Key words: iatrogenic compression-toxic lesions of the lower alveolar nerve, neuron-specific enolase, protein S100, resorcinol-formalin, epoxy resin, hydrochloride amantadine.